A Bandwidth Degradation Technique to Reduce Call Dropping Probability in Mobile Network Systems - CH. Monica; K.V.L. Bhavani (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A generic video telephony may require more than 40 kbps whereas a low motion video telephony may require about 25 kbps for data transmission. From the designing point of view these requirements demands for an alternative resource planning, especially for bandwidth allocation in wireless networks. In wireless network where bandwidth is a scare resource, the system may need to block incoming user if all of the bandwidth has been used to provide highest quality of service to existing users. However this bandwidth resource planning may be unacceptable for larger application. This work aims towards a realization of a mobile network using W-CDMA multi access technique supporting multilevel quality of services. The bandwidth allocation to multiple users is adjusted dynamically according to the required network condition so as to increase bandwidth utilization. The work analyzes the performance deriving the degradation period ratio, mean degradation time and degradation state for the implemented wireless network. The proposed work is aim to implement on Matlab tool for its functional verification considering various mobility patterns.